Metronomic oral vinorelbine in advanced breast cancer and non-small-cell lung cancer: current status and future development. (February 2016) - Cazzaniga, Marina E; Camerini, Andrea; Addeo, Raffaele; Nolè, Franco; Munzone, Elisabetta; Collovà, Elena; Del Conte, Alessandro; Mencoboni, Manlio; Papaldo, Paola; Pasini, Felice; Saracchini, Silvana; Bocci, Guido
Metronomic chemotherapy (mCT), a frequent administration of low-dose chemotherapy, allows prolonged treatment duration and minimizes the toxicity of standard-dose chemotherapy. mCT has multiple actions against cancer cells including inhibition of angiogenesis and modulation of the immune system. A number of studies lend support to the clinical efficacy of mCT in advanced breast cancer and non-small-cell lung cancer. However, further evidence is necessary to describe the optimal use of mCT and to identify suitable patients. Oral vinorelbine has emerged as a promising metronomic treatment in patients with metastatic breast cancer and non-small-cell lung cancer and is the only orally available microtubule-targeting agent. This paper reviews current evidence on metronomic oral vinorelbine, discusses its management and defines a suitable patient profile on the basis of a workshop of Italian experts.